Upaya Membentuk Karakter Anak Sekami di Lingkungan Waitiu Paroki Santo Alfonsus Maria De Liguori Melalui Kegiatan Keagamaan - Yosep Belen Keban; Mateus Dangga (Sekolah Tinggi Pastoral Kateketik Santo Fransiskus Assisi, 2024)
The activities of Dedication to the Society (PkM) with the aim of educating the children of Sekami in the Waitiu Parish of St. Alfonsus Maria de Liguori Lewotala are important activities for shaping the character of children of the Sekami. This is done because today many Sekami children are trapped in life behaviors that deviate from Christian teachings like stealing, making dirty words, disrespecting parents, teachers and peers, not engaging in spiritual activities and so on. The activity aims to cultivate and shape the character of the Sekami children in the Waitiu Parish of St. Alfonsus Maria de Liguori Lewotala through religious education activities. The method in this devotional activity is in the form of cultivation and education to the children of Sekami through presence, involvement and also sharing of faith. This dedication takes place every Saturday afternoon in May 2024. The result of this activity is the children of the Waitiu Parish of St. Alfonsus Maria de Liguori Lewotala.becoming increasingly aware and growing in himself the Christian character of life by engaging in various activities programmed by animators-animatrists in order to make himself a superior human being later on who is firmly attached to Christian teachings.